The Effect of Regional Budget Planning and Realisation on the Human Development Index in North Gorontalo Regency, Gorontalo Province - Deisy Sandra Maryana Datau; Zuchri Abdussamad; Muchtar Ahmad (Ilomata International Journal of Social Science, 2026)
This research is intended to examine the effect of Regional Budget Planning (APBD Planning) and Regional Budget Realization (APBD Realization) on Human Development Index (HDI) in North Gorontalo Regency. The research was in response to the importance of budget management strategy for an increase in public welfare and funding resources that are channeled through education, health, and living standard. The study is based on a quantitative survey research. The data were gathered by surveying the 67 respondents (Regional Government Budget Team (TAPD) and Regional House of Representatives Budget Committee members). Partial and simultaneously effects of APBD Planning and APBD Realization on HDI were analyzed with multiple linear regression using SPSS 25. The findings reveal that APBD Planning has a positive and significant impact on HDI, indicating the better quality of planning processes leads to higher human development. APBD Realization also has a positive and significant impact on HDI, indicating that high efficiency of budget absorption ensures good public services and the welfare of the community. At the same time, both variables have a significant effect on HDI with F value = 22.492 and R² = 0.413 indicating that the variation of budget planning and realization explains 41.3% of variation in HDI. This research is constrained by the fact that purposive sampling was used and it only concentrated on one regional government. The study can be further extended by increasing the sample size or the number of regions to improve the generalizability. Results show the need to intensify the accuracy of budget planning, enhance implementation mechanisms and promote prompt absorption of priority programs for maximization of development results. This study adds to the literature by providing evidence of the implementation at regional level in Indonesia by investigating how planning and realization of budget directly affects performance of human development, which has been limited exploration in local fiscal policy research.